Analisis Perlindungan Hukum Terhadap Debitur Dalam Transaksi Pinjaman Online Di Aplikasi Adakami - Rudyanto Benyamin Hendika Katoda; Darius Mauritsius; Husni Kusuma Dinata (Artemis Law Journal, 2026)
One of the innovations that emerged from this progress is the presence of online loan services. Effective and efficient online loan services provide convenience for people to access loan funds. The problem that often occurs is because high interest rates make it difficult for borrowers to pay off the debt, then get terror from debt collectors so that there are customers who prefer to end their lives. So the author conducted this study with the aim of: 1) To find out and analyze the legal protection provided to debtors in online loan transactions through the AdaKami application based on the laws and regulations in force in Indonesia. 2) To find out and analyze legal protection for debtors related to debt collection practices that carry out interest terror actions that are not in accordance with the contents of the agreement on the AdaKami application. This study uses a normative legal research type. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials which are then analyzed descriptively analytically. The results of the study show the existence of regulations governing the legal protection provided to debtors in online loan transactions and the lack of legal protection for debtors related to debt collection practices that carry out interest terror actions that are not in accordance with the contents of the agreement on the service.